NORMATIVE INSTITUTIONALIZATION OF CLIENT ORIENTATION IN THE PUBLIC ADMINISTRATION SYSTEM OF THE REPUBLIC OF KAZAKHSTAN: PROBLEMS AND IMPLEMENTATION PROSPECTS - Kusherbayev, Адилет Муратович; Dulambayeva , Раушан Тлегеновна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2025)
The article examines the formal legal establishment of the client orientation principle in Kazakhstan’s public administration. The study aims to assess the extent of institutionalization of this principle in current legislation and strategic documents, and to determine whether existing mechanisms ensure its practical implementation. The research employs analysis of strategic programs, conceptual policy documents, and legal acts that reflect the orientation of public administration toward citizen needs. The analysis shows that the client orientation principle is affirmed in high-level policy documents (e.g., the “Kazakhstan–2050” Strategy, the Public Administration Development Concept until 2030, the Civil Service Development Concept 2024–2029) and in certain laws (for example, the Law “On Public Services”), but its legal institutionalization remains fragmented. The study pays special attention to digitalization as a tool for implementing a client-oriented approach. It finds that the digitalization of public services is often limited to technical improvements without a fundamental rethinking of public service goals and principles. The need to distinguish between individual and public interests in designing government services is substantiated, along with the institutionalization of citizen feedback mechanisms and consideration of citizen opinions in evaluating government performance. Practically, the findings can inform legislative reforms and the introduction of client-oriented mechanisms in the public sector. It is concluded that client orientation is only partially realized in Kazakhstan’s public administration, and recommendations are provided to strengthen the regulatory framework to transform this principle from declarative to effective.